The movement of conscientious objection and total objection in Spain (1971-2002) - Oliver Olmo, Pedro (Hispania Nova, 2021)
We provide a synthesis and analysis of the mobilisation against military service and militarism in late XX century Spain. This mobilisation is considered as a new social movement that developed a cycle of three decades of mobilisation, subdivided into six stages between 1971 and 2002. The conscientious objectors, basing themselves on nonviolence, built an identity and ideological consensus that persisted thanks to the uninterrupted continuity of the foundational group, the Conscientious Objection Movement (MOC). In the 1980s, the mobilisation diversified with the creation of the Mili KK. But beyond their rivalry and coordination, the antimilitarist groups shared two fundamental values: antimilitarism and civil disobedience. Historically speaking, their singular character was due to their perseverance in practicing civil disobedience, thanks to which they managed to accentuate the unpopularity of military service and bring about the crisis of the recruiting system.